Influence of sports asymmetry and ambidexterity of ground wrestling on the level of competitive performance of Greco-Roman style wrestlers - Nagovitsyn, R.; Zhuikova, S.; Kondratiev, N.; Osipov, A.; Zhavner, T.; Vapaeva, A. (Journal of Physical Education and Sport, 2018)
In our studies, the purpose of our research was to determine the level of dependence of the competitive results of Greco-Roman wrestlers with their ability to realize technique in the ground wrestling in different directions. Actually the participants of the research are the athletes (n = 160) with different sports qualifications from the beginners (B) to subelite (S) and elite athletes (High sports mastery (HSM)). Moreover, the athletes were divided into 2 groups: group of athletes with asymmetry (AG) (n=99) - the athletes conducting holds in the ground mainly in one direction and group of athletes with ambidexterity (AmG) (n=61) - the athletes conducting holds both the right and left sides. The study period is 2 years (2015-2016). By the way the competitive results of the athletes were assessed using the rating scale developed by the authors. On average, the number and quality of techniques of the ground wrestling was assessed by the method of competitive matches analyses. Besides the statistical analysis was performed using Student's t-test. Besides, it was revealed that the elementary education athletes (B) performing ground wrestling holds predominantly in one direction so their competitive results are reliable higher (P<0,01). It should be noted that an approximate equality of the competitive results of the subelite athletes (S) is recorded in the group of athletes (AG) and group of athletes (AmG). The level of competitive results of the elite athletes (HSM) is significantly (P<0,01) higher than the wrestlers of the group of athletes (AmG). Indeed, the results show that the ability to conduct holds successfully in the ground in different directions does not have a significant effect on sports results of the athletes at the initial stage of preparation. Fortunately, this ability allows the elite wrestlers to increase the level of sports results significantly.